GMAT Question of the Day - Daily to your Mailbox; hard ones only

 It is currently 20 Jun 2019, 12:32 GMAT Club Daily Prep

Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.  If f(2x - 1) = 4x² - 4x - 8, then f(5) =

Author Message
TAGS:

Hide Tags

CEO  V
Joined: 12 Sep 2015
Posts: 3786
If f(2x - 1) = 4x² - 4x - 8, then f(5) =  [#permalink]

Show Tags

2
Top Contributor
5 00:00

Difficulty:   15% (low)

Question Stats: 73% (01:17) correct 27% (01:37) wrong based on 125 sessions

HideShow timer Statistics

If f(2x - 1) = 4x² - 4x - 8, then f(5) =

A) 16
B) 18
C) 36
D) 48
E) 72

_________________
Director  P
Joined: 31 Jul 2017
Posts: 516
Location: Malaysia
GMAT 1: 700 Q50 V33 GPA: 3.95
WE: Consulting (Energy and Utilities)
Re: If f(2x - 1) = 4x² - 4x - 8, then f(5) =  [#permalink]

Show Tags

1
GMATPrepNow wrote:
If f(2x - 1) = 4x² - 4x - 8, then f(5) =

A) 16
B) 18
C) 36
D) 48
E) 72

$$f(2x-1) = 4(x+1)(x-2)$$...... When $$x = 3, f(5) = 16.$$
_________________
If my Post helps you in Gaining Knowledge, Help me with KUDOS.. !!
VP  D
Status: Learning stage
Joined: 01 Oct 2017
Posts: 1009
WE: Supply Chain Management (Energy and Utilities)
Re: If f(2x - 1) = 4x² - 4x - 8, then f(5) =  [#permalink]

Show Tags

1
GMATPrepNow wrote:
If f(2x - 1) = 4x² - 4x - 8, then f(5) =

A) 16
B) 18
C) 36
D) 48
E) 72

When x=3, 2x-1=5

So,$$f(2x-1)=f(5)=4*3^2 - 4*3 - 8=36-12-8=16$$.

Ans. (A)
_________________
Regards,

PKN

Rise above the storm, you will find the sunshine
Senior Manager  P
Joined: 07 Jul 2012
Posts: 372
Location: India
Concentration: Finance, Accounting
GPA: 3.5
Re: If f(2x - 1) = 4x² - 4x - 8, then f(5) =  [#permalink]

Show Tags

1
f(2x-1)= f(5); when x=3

Put x=3 in the equation 4$$x^2$$ -4x - 8. The answer is 16.

_________________
Kindly hit kudos if my post helps!
Math Expert V
Joined: 02 Aug 2009
Posts: 7756
Re: If f(2x - 1) = 4x² - 4x - 8, then f(5) =  [#permalink]

Show Tags

GMATPrepNow wrote:
If f(2x - 1) = 4x² - 4x - 8, then f(5) =

A) 16
B) 18
C) 36
D) 48
E) 72

Another way.. May help in such questions somewhere else..

If you look at the equation, you can easily convert the equation ...
$$f(2x-1)=4x^2-4x-8=4x^2-4x+1-9=(2x-1)^2-9$$
So it can be literally written as $$f(x)=x^2-9$$,
So f (5)=5^2-9=25-9=16
_________________
Manager  B
Joined: 29 Jul 2018
Posts: 114
Concentration: Finance, Statistics
GMAT 1: 620 Q45 V31 Re: If f(2x - 1) = 4x² - 4x - 8, then f(5) =  [#permalink]

Show Tags

1
2
Equate 2x-1 = 5 you get x=3
Put x=3 36-8-12
16

Posted from my mobile device
Senior Manager  V
Joined: 22 Feb 2018
Posts: 428
Re: If f(2x - 1) = 4x² - 4x - 8, then f(5) =  [#permalink]

Show Tags

OA: A

f(2x - 1) = 4x² - 4x - 8, then f(5) = ?

Trying lengthier method as other methods have been already discussed above

Let $$2x-1 =y ; x =\frac{y+1}{2}$$

$$f(y) = 4(\frac{y+1}{2})^2 -4 (\frac{y+1}{2}) -8 =(y+1)^2-2(y+1)-8 =y^2+1+2y-2y-2-8=y^2-9$$

$$f(y)=y^2-9$$

$$f(5) =5^2-9=25-9=16$$
_________________
Good, good Let the kudos flow through you
VP  G
Joined: 09 Mar 2018
Posts: 1003
Location: India
Re: If f(2x - 1) = 4x² - 4x - 8, then f(5) =  [#permalink]

Show Tags

GMATPrepNow wrote:
If f(2x - 1) = 4x² - 4x - 8, then f(5) =

A) 16
B) 18
C) 36
D) 48
E) 72

to find f(5), never go ahead and put the value as 5 in f(2x-1)

Think how can i get a f(5), when i substitute x = 3

f(5) =36 - 20
= 16

A
_________________
If you notice any discrepancy in my reasoning, please let me know. Lets improve together.

Quote which i can relate to.
Many of life's failures happen with people who do not realize how close they were to success when they gave up.
CEO  V
Joined: 12 Sep 2015
Posts: 3786
If f(2x - 1) = 4x² - 4x - 8, then f(5) =  [#permalink]

Show Tags

Top Contributor
GMATPrepNow wrote:
If f(2x - 1) = 4x² - 4x - 8, then f(5) =

A) 16
B) 18
C) 36
D) 48
E) 72

Great responses above!! Here's one more approach:

First notice that 4x² - 4x - 8 looks a lot like (2x - 1)²

(2x - 1)² = (2x - 1)(2x - 1) = 4x² - 4x + 1

Now take: f(2x - 1) = 4x² - 4x - 8
Rewrite as: f(2x - 1) = 4x² - 4x + 1 - 9 = (2x - 1)² - 9
In other words, f(something) =something² - 9

In general, we can write f(x) = x² - 9

So f(5) = 5² - 9 = 25 - 9 = 16

Cheers,
Brent
_________________ If f(2x - 1) = 4x² - 4x - 8, then f(5) =   [#permalink] 18 Apr 2019, 08:35
Display posts from previous: Sort by

If f(2x - 1) = 4x² - 4x - 8, then f(5) =  